Dioxin environmental fate and health/ecological consequences - Kurwadkar, Sudarshan, 1973- (Boca Raton : CRC Press LLC, 2020)
Dioxin - Environmental Fate and Health/Ecological Consequences offers a unique, and comprehensive coverage of dioxins and their congeners once they are released to the environment. The book provides readers with a systematic understanding of past and emerging sources of dioxins, current dioxins inventories and historical trends, fate and long-range transboundary atmospheric transport, human health, and ecological risk and regulatory perspective. Providing an excellent analysis of dioxin exposure through the food chain and impact on human health, it also documents the environmental implications of dioxins on ecological flora and fauna. The book offers readers a holistic understanding about dioxins, their atmospheric fate and transport, distribution in various environmental matrices and various routes and exposure pathways through which human beings are exposed to this persistent organic pollutant. It further offers an insight into the toxicological profile and mechanistic analysis of the onset of cancer, remediation technologies, and existing regulatory framework to deal with the problems associated with dioxins. The book will serve as an excellent resource to environmental professionals, particularly environmental toxicologists, environmental health professionals, remediation engineers, environmental regulatory agencies, policymakers, and environmental law professionals.
OCLC-licensed vendor bibliographic record.
Keywords: Dioxins -- Environmental aspects; SCIENCE / Chemistry / General; SCIENCE / Environmental Science; TECHNOLOGY / Engineering / Civil